Anticorrosive Performances Of Natural Additives Extracted From Organic Compounds Based Hybrid Epoxy Coating On Steel - R.Venkatakrishnan, P.K.Dinesh, B.Balaji (International Journal of Modern Agriculture, 2021)
Corrosion is the nature process. Due to corrosion many steel materials losses day by day. There are various method to avoid corrosion in steel by using coating. In our work we do epoxy coating on steel by spray coating. Epoxy coating widely apply on steel structures due to their higher adhesion strength and epoxy coating have corrosion resistant properties. In existing epoxy coating done in inorganic compounds are used. We do epoxy coating by using organic compounds such as orange peel, neem leaf, and cashew nut. Taking extracts from organic compounds filter by using muslin cloth and corrosion testing is done which is salt spray corrosion test and water absorption test. There is no corrosion inhibitory in the coated steel. Compare to other methods epoxy coating give better performances.